2022
DOI: 10.3390/horticulturae8090782
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Selenium and Methyl Jasmonate Controls Postharvest Tomato Gray Mold by Damaging the Membrane System

Abstract: Tomato, which is regarded as an important worldwide crop, is susceptible to gray mold caused by Botrytis cinerea. Selenium and methyl jasmonate can act as antifungal agents against pathogenic infections. To clarify the effect of selenium and methyl jasmonate on the fungal pathogen, the spore germination and mycelial growth of B. cinerea were investigated in vitro using the growth rate method. Additionally, the electrical conductivity, soluble protein content, malondialdehyde content and oxalic acid secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Among all groups, the MDA content and membrane permeability of cherry tomatoes treated with the composite coating were relatively low (Figure 5a,b). This suggested that the senescence degree of cherry tomatoes treated with the composite coating was the lowest, and also confirmed that free radical scavenging enzymes played a positive role [31]. The CHI and GLU activities of postharvest cherry tomatoes treated with the composite coating maintained the highest activity during the whole storage period (Figure 4d,e).…”
Section: Discussionsupporting
confidence: 62%
“…Among all groups, the MDA content and membrane permeability of cherry tomatoes treated with the composite coating were relatively low (Figure 5a,b). This suggested that the senescence degree of cherry tomatoes treated with the composite coating was the lowest, and also confirmed that free radical scavenging enzymes played a positive role [31]. The CHI and GLU activities of postharvest cherry tomatoes treated with the composite coating maintained the highest activity during the whole storage period (Figure 4d,e).…”
Section: Discussionsupporting
confidence: 62%
“…Se, an essential micronutrient for both humans and plants, is suggested to be involved in gray mold resistance, supported by increasing evidence. In vitro, it has been shown that 24 mg/L Se treatment markedly suppressed the spore germination of B. cinerea [17]; in vivo, Se treatment, alone or combined with other chemicals such as melatonin and methyl jasmonate, could effectively control tomato postharvest gray mold, either by increasing the antioxidant enzyme activities or damaging the membrane structure of the pathogen [43][44][45]. In our study, 12 mg/L treatment was shown to significantly control the gray mold disease of postharvest strawberry fruit.…”
Section: Exogenous-se Application Enhanced the Tolerance Of Strawberr...mentioning
confidence: 99%
“…Generally, after infection with B. cinerea, the yield of tomatoes decreases by 20%-30%, and for severely affected plots can even be as high as 50%. 30,31 In recent years, ULV spraying is considered a most effective and labor-saving technique for the control of high humidity-induced vegetable disease, such as tomato gray mold. Compared with traditional mechanical and manual pesticide spraying, the use of ULV sprayers can save labor and time, while enabling pest and disease control without significant impacts on yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Such environmental conditions in the greenhouse favor the occurrence of B. cinerea , and it is not easy to control. Generally, after infection with B. cinerea , the yield of tomatoes decreases by 20%–30%, and for severely affected plots can even be as high as 50% 30,31 …”
Section: Introductionmentioning
confidence: 99%